A Case of Unsuspected Peritoneal Mesothelioma Occurring with Colonic Adenocarcinoma Masquerading as Peritoneal Metastases - Wei Xie; Linda K. Green; Rishi A. Patel; Syeling Lai (Hindawi Limited, 2014)
We report a case of synchronous primary colonic adenocarcinoma and malignant mesothelioma. A 61-year-old male presented with a six-month history of fatigue and weight loss. An abdominal computed tomography (CT) scan showed a 5.8 cm partially obstructing mass in the cecum with ascites and peritoneal thickening. A biopsy of the large mass showed an adenocarcinoma. Because the patient was clinically thought to be a T4 colon carcinoma with peritoneal metastatic lesions (M1), prior to initiating chemotherapy, a debulking right hemicolectomy was performed. Resection of the colon and ileum revealed a T3N0 colonic mucinous adenocarcinoma and concurrent diffuse malignant peritoneal mesothelioma. Presenting synchronous colonic and peritoneal mesothelial primary malignancies are exceedingly rare but must be considered to prevent incorrect clinical staging.